2 - Subjecting Nature to Central Authority: The Struggle over Public Goods in the Formation of Citizenship: by Nyangabyaki Bazaara - Bazaara, Nyangabyaki (Africa Development, 2006)
Uganda is widely cited for its participatory orientation and strong commitment to implementation with regard to its decentralisation reforms. The implementation and outcomes of Uganda’s decentralisation reforms are examined to test the assumption that when decision-making powers over the environment are devolved to locally elected representatives, this increases participation and leads to better environmental outcomes. This article’s analysis accounts for actors who have received environmental powers, the central–local government relations, the local government relationship with local population, and social and environmental outcomes. Evidence indicates that collaborative management schemes lack decision-making powers and fail to represent all groups with interest in the resources. The centre retains control of natural resources through deconcentrated functions that are not accountable to the interests of local populations. Under such conditions it is not possible to test whether greater participation leads to better social and environmental outcomes, although it is evident that the current resource management arrangement does not favour sustainable environmental or better social outcomes.